The Influence of the Project Based Learning Model and Learning Motivation on Fourth Grade Elementary Students’ Narrative Writing Skills - Ainun Nisa'; Elfia Sukma; Yeni Karneli; Muhammadi Muhammadi (FKIP - Universitas Riau, 2026)
This study was conducted based on the low level of narrative writing skills among elementary school students, which is influenced by less innovative instructional models and low learning motivation. This study aimed to analyze the effect of the Project Based Learning (PjBL) model and learning motivation on the narrative writing skills of fourth-grade elementary school students. This research used a quantitative approach with a quasi-experimental method and a 2×2 factorial design. Data were collected through a narrative writing test and a learning motivation questionnaire, and analyzed using t-test and two-way ANOVA. The results showed that students in the PjBL class achieved higher mean scores, with 89.05 for high motivation and 73.15 for low motivation, compared to 80.21 and 52.64 in the conventional class. The ANOVA test indicated no significant interaction (Sig. = 0.537 > 0.05). It can be concluded that PjBL effectively improves narrative writing skills, while motivation acts as an independent factor.